2011
DOI: 10.1038/leu.2011.200
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications and molecular associations of NADH dehydrogenase subunit 4 (ND4) mutations in acute myeloid leukemia

Abstract: To study the prevalence and prognostic importance of mutations in NADH dehydrogenase subunit 4 (ND4), a mitochondrial encoded transmembrane component of the electron transport chain respiratory Complex I, 452 AML patients were examined for ND4 mutations by direct sequencing. The prognostic impact of ND4 mutations was evaluated in the context of other clinical prognostic markers and genetic risk factors. In all, 29 of 452 patients (6.4%) had either somatic (n ¼ 12) or germline (n ¼ 17) ND4 mutations predicted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 43 publications
4
31
3
Order By: Relevance
“…In contrast to findings in adult AML (Damm et al , ), evaluation of heteroplasmic and homoplasmic MT‐ND4 subtypes separately revealed no survival advantage for heteroplasmic MT‐ND4 variant paediatric AMLs ( P = 0·73, Fig S2). This apparent contradiction between these two studies may be due to limited frequencies of MT‐ND4 variant positive AML subjects in the present study.…”
Section: Mt‐nd4 Sequence Variants From the Total Paediatric Aml Cohorcontrasting
confidence: 83%
See 2 more Smart Citations
“…In contrast to findings in adult AML (Damm et al , ), evaluation of heteroplasmic and homoplasmic MT‐ND4 subtypes separately revealed no survival advantage for heteroplasmic MT‐ND4 variant paediatric AMLs ( P = 0·73, Fig S2). This apparent contradiction between these two studies may be due to limited frequencies of MT‐ND4 variant positive AML subjects in the present study.…”
Section: Mt‐nd4 Sequence Variants From the Total Paediatric Aml Cohorcontrasting
confidence: 83%
“…In accordance with previous observations in adult AML, homoplasmic F50L (UPN7), S86N (UPN8), and A131T (UPN10 + 11) variants were each defined as germline in paediatric AML samples because only variant mitochondrial DNA was detected in leukaemic and complete remission samples. Similarly, the heteroplasmic one base‐pair deletion (m.(11 032_11 038)delA) was determined to be somatic in paediatric AML case UPN4 as only leukaemia cells harboured the deletion (Fig B), confirming the results observed in adult AML (Damm et al , ).…”
Section: Mt‐nd4 Sequence Variants From the Total Paediatric Aml Cohorsupporting
confidence: 81%
See 1 more Smart Citation
“…In this line, during the past years it has become clear that the concept of a two-hit event in leukemia with a classical 'type 1' (proliferation) and 'type 2' (differentiation) mutation 46 cannot fully explain all recent findings on molecular mutations. More and more mutations have been shown to be important for the development of leukemia including alterations in genes relevant for genomic stability like TP53, 47 metabolic enzymes (IDH1, IDH2, ND4) 5,48,49 or proteins with effects on epigenetic modification (TET2, EZH2, DNMT3A) 50,51 . 52 This leads to a high probability of multiple mutations from different pathways are randomly combined and thereby underlie the pathogenesis of AML.…”
Section: Discussionmentioning
confidence: 99%
“…However, additional alterations occur in genes encoding proteins that it is too early to classified into these defined categories, such as DIS3, DDX41 [23], mitochondrial NAPDH dehydrogenase ND4 [62], or cohesin complex proteins [23,63]. …”
Section: Reviewmentioning
confidence: 99%